Antibody Response to Cutaneous Leishmaniasis in Sudan - Abushama, Hind Mohamed; Wahab, Maathr Ibrahim Abdel; Elhassan, Ahmed Mohamed; Osman, Omran Fadl; Mohamed, Hiba Salah-Eldin (The International Journal of Biotechnology, 2014)
The role of antibody levels in protective immunity against cutaneous leishmaniasis (CL) is largely unknown. The aim of this study is to investigate the role of antibody response against CL among Sudanese population. Fifty six clinically diagnosed CL subjects were enrolled in this study. Forty eight of them had healed scar and eight have active lesions. The leishmanin skin test (LST) was 54.7% positive. The frequency of human IL4RP2 alleles was investigated in this study. The results showed 83.9% (183 bp) and 16.1% (253 bp) and the heterozygosity was 39%. The mean antibody levels using direct agglutination test (DAT) has found to be higher against Leishmania major (L. major) antigen than Leishmania donovani (L. donovani) antigen and the difference was found to be significant (P = 0.01 <0.05). The anti L. major IgG was quantified in this study using enzyme linked immunosorbent assay (ELISA). The mean of antibody levels measured by ELISA and DAT was significantly higher in study participants with scars more than those with skin lesions. Overall this outcome would be supportive to indicate a possible role of antibody-mediated protection in CL and would signify the importance of identification of antigens that may elicit protective antibodies.